2022
DOI: 10.3389/fmicb.2022.849883
|View full text |Cite
|
Sign up to set email alerts
|

Similar Carcass Surface Microbiota Observed Following Primary Processing of Different Pig Batches

Abstract: Bacterial contamination during meat processing is a concern for both food safety and for the shelf life of pork meat products. The gut microbiota of meat-producing animals is one of the most important sources of surface contamination of processed carcasses. This microbiota is recognized to vary between pigs from different farms and could thus be reflected on the bacterial contamination of carcasses at time of processing. In this study, the microbiota of 26 carcasses of pigs originating from different farms (i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 45 publications
0
10
1
Order By: Relevance
“…As the slaughter process is thought to present very little variation, it is possible to hypothesize that the differences in the mean relative abundance as well as in alpha and beta diversity are mainly supported by the arrival of different inputs (carcasses) in the cutting room, by the staff working during these different days, and by differences in the application of washing and disinfection measures. However, a study by Braley et al, conducted in the same facility as our study, revealed no significant difference of microbiota between pig carcass batches [ 46 ]. The fact that the study conducted by Braley et al was realized during a short period of time (one day) and the sampling in our study took place at monthly intervals could explain these variations in the impact of time.…”
Section: Discussioncontrasting
confidence: 55%
“…As the slaughter process is thought to present very little variation, it is possible to hypothesize that the differences in the mean relative abundance as well as in alpha and beta diversity are mainly supported by the arrival of different inputs (carcasses) in the cutting room, by the staff working during these different days, and by differences in the application of washing and disinfection measures. However, a study by Braley et al, conducted in the same facility as our study, revealed no significant difference of microbiota between pig carcass batches [ 46 ]. The fact that the study conducted by Braley et al was realized during a short period of time (one day) and the sampling in our study took place at monthly intervals could explain these variations in the impact of time.…”
Section: Discussioncontrasting
confidence: 55%
“…The detection of Salmonella spp. was based on the methods used in previous studies [ 38 , 39 ]. Briefly, thawed samples were cultured on Modified Semi-Solid Rappaport-Vassiliadis Agar (MSRV) (Biokar diagnostic) as a selective enrichment step and two selective media: Brilliant Green Sulfa (BD Difco, Franklin Lakes, NJ, USA) agar and Xylose-Lysine-Desoxycholate (Biokar diagnostic) agar.…”
Section: Methodsmentioning
confidence: 99%
“…A 291 pb fragment of the V4 region of the 16S rRNA gene was amplified by PCR using universal primers 515F_III (5′-ACACTGACGAACTGGTTCTACAAGTGCAGCMGCCGCGGTAA-3′) and 806R_III (5′-TACGGTAGCAGAGACTTGGTCTGGACTACHUGGGTWTCTAAT-3′) (Invitrogen, Thermo Fisher Scientific, Waltham, MA, USA). A 30 μL PCR reaction assessment was performed using the Platinum SuperFi PCR Master Mix (Invitrogen, Burlington, ON, Canada), as previously described [ 39 ]. The PCR program consisted of an initial denaturation at 95 °C for 5 min, followed by 25 cycles of amplification that included a denaturation step at 95 °C for 30 s, an annealing step at 55 °C for 30 s, an elongation step at 72 °C for 60 s, and a final elongation step of 10 min at 72 °C in a Mastercycler ® Nexus PCR (Eppendorf AG, Hamburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations